2019
DOI: 10.1007/s40089-018-0262-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and cytotoxicity of polyethylene glycol-encapsulated CdTe quantum dots

Abstract: Semiconductor quantum dots (QDs) offer tremendous scope to be used in the field of energy, imaging, sensors and optoelectronic devices. However, several issues regarding their hydrophilicity, stability and cytotoxicity remain unresolved. One of the methods to render CdTe QDs water-soluble is to functionalize the surface with carboxylate groups by the use of heterobifunctional ligands such as 3-mercaptopropionic acid (MPA). Following this motif, we report the synthesis of CdTe QDs using the non-aqueous organome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…At present, the concentration of QDs is determined by many ways: (1) quantifying a specific element of QDs to determine the concentration (For example, using Cd element to quantify the concentration of CdTe QD) (He et al, 2018; Wu, Liang, He, Wei, Wang, Zou, et al, 2018); (2) weighing the mass of freeze‐dried powder of QDs (especially carbon‐based QDs) (Murugan et al, 2017; Singh et al, 2012); (3) measuring the absorbance and using Beer's Law to calculate the molar concentration (Ali et al, 2019; Han et al, 2019). In addition, QDs are atomic clusters composed of a variety of elements, and they are not fixed, single and pure compounds.…”
Section: Cytotoxicity Of Qdsmentioning
confidence: 99%
“…At present, the concentration of QDs is determined by many ways: (1) quantifying a specific element of QDs to determine the concentration (For example, using Cd element to quantify the concentration of CdTe QD) (He et al, 2018; Wu, Liang, He, Wei, Wang, Zou, et al, 2018); (2) weighing the mass of freeze‐dried powder of QDs (especially carbon‐based QDs) (Murugan et al, 2017; Singh et al, 2012); (3) measuring the absorbance and using Beer's Law to calculate the molar concentration (Ali et al, 2019; Han et al, 2019). In addition, QDs are atomic clusters composed of a variety of elements, and they are not fixed, single and pure compounds.…”
Section: Cytotoxicity Of Qdsmentioning
confidence: 99%
“…Covalent functionalization of silicon QDs with phenanthrene, pyrene, and perylene chromophores (Abdelhameed et al 2018) effectively tuned the emission color as well as enhanced the emission quantum efficiency. In order to enhance their water solubility and thus biocompatibility, QDs can be coated with hydrophilic ligands (such as thiolate alcohols, thiolate acids and thiolate siloxane acids (Zhou et al 2017), or monothiol ligands including 3-mercaptopropionic acid (MPA) (Ali et al 2019) and mercaptoundecanoic (MUA)), amphiphilic polymers (such as polyethylene glycol (Susumu et al 2009), poly(N-isopropylacrylamide) (Hu and Gao 2010)), or silica (Cao et al 2020;Hu and Gao 2010). Besides these, glutathione (Aydemir et al 2020), bovine serum albumin (Barba-Vicente et al 2020;Sahoo et al 2019), poly(lactic-co-glycolic acids), and chitosan (Kharkar et al 2020) were also reported to promote the biocompatibility of QDs.…”
Section: Introductionmentioning
confidence: 99%
“…QDs potential toxicity can also be limited by surface modification, like adding PEG [86] or carbohydrate to QDs [87], [88]. In this contest, recently, cadmium-free QDs (Cd-free QDs) made of indium/palladium were amply used because of their higher biocompatibility [89], [90].…”
Section: Quantum Dots (Qds)mentioning
confidence: 99%